The haematuria clinic--referral patterns in Northern Ireland. - Ho, E. T. (Ulster Medical Society, 1998)
One hundred consecutive patients with haematuria were seen over a three month period at the haematuria clinic, Belfast City Hospital. 14% of patients were found to have transitional cell carcinoma of the urinary bladder; all of these presented with frank haematuria and were over 50 years of age. No malignancy was detected in the microscopic haematuria group. 14% of patients with macroscopic haematuria held back for longer than one month before seeking advice from their general practitioner. 23% with macroscopic and 30% with microscopic haematuria had their symptoms noted by the general practitioner for more than a month before they were referred for investigation. The waiting time for initial investigation at the haematuria clinic took longer than six weeks in 52% with macroscopic and 39% with microscopic haematuria. Our study has identified a high-risk group who need immediate referral and investigation. The importance of patient education, rapid referral by general practitioners and also the need to increase the capacity of the haematuria clinic are emphasized.